The “Surprise Question” in Neurorehabilitation—Prognosis Estimation by Neurologist and Palliative Care Physician; a Longitudinal, Prospective, Observational Study - Ebke, Markus; Koch, Andreas; Dillen, Kim; Becker, Ingrid; Voltz, Raymond; Golla, Heidrun (Frontiers in Neurology, 2018)
Background: The 12-months ‘surprise’ question (12-SQ) for estimating prognosis and the need for integrating palliative care (PC) services has not yet been investigated for neurological patients. Objective: Test the value of the 12-SQ on a sample of neurorehabilitation patients. Methods: All patients newly registered in the Department of Neurorehabilitation, Dr. Becker Rhein-Sieg-Clinic (8/2016-03/2017) were asked to participate. The treating neurorehabilitation physicians (NP) and an external consulting PC physician (PCP) independently estimated patients’ prognosis using the 12-SQ; while symptom burden was independently assessed using the standardized palliative outcome measurement HOPE-SP-CL, a set of additional neurological issues, and ECOG. Follow-up with consenting patients twelve months later was via telephone. Descriptive and inferential statistics were utilized in data analysis. Results: Of 634 patients, 279 (44%) patients (male: 57.7%, female: 42.3%; mean age: 63 ± 14) (or, alternatively, their legal representative) consented and were assessed at baseline. Per patient NP and PCP both answered the 12-SQ with “Yes” (164), with “No” (42), or had different opinions (73). The “No” group displayed the highest symptom burden on all three measures for both disciplines. Overall, PCP scored higher (i.e. worse) than NP on all measures used. Follow-up was possible for 236 (drop-out: 15.4%) patients (deceased: 34 (14.4%), alive: 202 (85.6%)). Baseline scores on all measures were higher for deceased patients compared to those still living. Prognostic characteristics were: sensitivity: NP 50%, PCP 67.6%; specificity: NP 86.1%, PCP 70.3%, p<0.001; positive predictive value: NP 37.8%, PCP 27.7%; negative predictive value: NP 91.1%, PCP 92.8%; area under the curve: NP 0.68, PCP 0.69; success rate: NP 80.9%, PCP 69.9%, p=0.002. Regression analysis indicated that age, dysphagia and overburdening of family (NP answering the 12-SQ), dysphagia and rehabilitation phase (PCP answering the 12-SQ) were associated with increased likelihood of dying within twelve months. Without the 12-SQ as relevant predictor, age, dysphagia and ECOG were significant predictors (NP and PCP). Conclusion: Combining the 12-SQ with a measurement assessing PC and neurological issues could potentially improve the 12-SQ’s predictive performance of twelve-month survival and help to identify when to initiate the PC approach. Clinical experiences influence assessment and prognosis estimation.